Examining Enactments of Project-based Learning in Secondary English Language Arts - Alison G. Boardman; Joseph L. Polman; Karla Scornavacco; Ashley Seidel Potvin; Antero Garcia; Bridget Dalton; Kristina Stamatis; Aaron Guggenheim; Jessica L. Alzen (SAGE Publishing, 2024)
Project-based learning (PBL) grounds instruction in authentic learning experiences where students engage in real-world explorations that culminate in a final product or performance. We report on a mixed methods study with 43 ninth-grade English language arts (ELA) teachers (22 PBL and 21 comparison) and 1,671 students exploring the feasibility of enacting PBL in ELA classrooms and examining how teachers and students perceived this approach to learning. PBL teachers enacted PBL design principles significantly more than comparison teachers. The majority of PBL teachers perceived positive instructional shifts including more student-centered and authentic learning, more student choice, and greater student engagement. Many teachers also expressed a sense of renewal and passion. Students in PBL classrooms reported more meaningful learning experiences, opportunities for collaboration, and other aspects of social and emotional learning. We discuss tensions, including the challenge of covering required content and skills within a PBL-focused classroom.